Navigating Academia : a guide for women and minority STEM faculty - Mosley, Pauline; Hargrove, S. Keith (Academic Press is an imprint of Elsevier, 2015)
Navigating Academia: A Guide for Women and Minority STEM Faculty explores the infrastructure of the academy and provides a systematic account of where and why women and minorities fall behind men in the preparation for and development of their academic careers. This book offers useful strategies for recruiting, retaining, and advancing women and minorities. Chapters include testimonials from faculty and administrators about how they made their ascent within the academy. Navigating Academia: A Guide for Women and Minority STEM Faculty also discusses how to modify and expand faculty recruiting.